Penerapan Latihan Pursed Lips Breathing Terhadap Perubahan Respiratory Rate Pasien Pneumonia Di RSUD Arifin Achmad - Rima Mustika; Riani Riani; Putri Eka Sudiarti (Excellent Health Journal, 2025)
Pneumonia is an infectious disease that affects the lower respiratory tract with signs and symptoms such as coughing and shortness of breath. Pneumonia, or inflammation of the lungs, can cause various serious impacts, including complications such as lung abscess, empyema, pleural effusion, respiratory failure, and even death. In addition, pneumonia can also cause pulmonary fibrosis and bronchiectasis, and increase the risk of kidney failure if complications such as sepsis occur. In An.M, the main complaint felt was that the mother said that 3 days ago before entering the hospital she had a cough with phlegm, shortness of breath and difficulty in expelling phlegm. The purpose of this scientific paper is to obtain an overview of nursing care by providing pursed lips breathing exercises. This study uses a direct observation method in assessing, analyzing data, and diagnosing patients with Pneumonia with one respondent, carried out at HCU Anggrek. The results of this nursing care showed that breathing began to return to normal. This shows that pursed lips breathing exercises can provide changes to breathing in Pneumonia patients. It is hoped that patients can apply pursed lips breathing exercises routinely with the hope that breathing in patients will return to normal.